Kamiltepe, Aserbaidschan: Ancient Kura – Kura in Motion - Helwing, Barbara (e-Forschungsberichte des DAI, 2023)
The 2012 campaign at Kamiltepe and MPS 4 yielded details on stratigraphical sequencing and internal chronology. New findings are a round structure cutting into the earlier platform, and cell-like rooms attached to the platform. At MPS 4 the two interior ditches could be traced over a longer section; by this, an upper occupation with oval hut floors as well as a lower ditch fill could be identified, both representing distinct chronological phases of occupation. In 2013, excavations at Kamiltepe completed the documentation of an empty area north of the platform and opened access to the platform façade. A large round building in the north, filled with a thick ash layer, had been disturbed by Iron Age burials. In MPS 4 the excavations within the two interior ditches yielded sections with and without finds, separated by walls within the ditches. Joining fragments of a female figurine indicate that both ditches were open at the same time; radiocarbon dated around 5600 BC.